Analisis Sistem Pendukung Keputusan Penerimaan Beasiswa Menggunakan Metode Simple Additive Weighting (Saw) Berbasis Web - Dwi Tiara Safitri; Sauri Fitriandini Hrp; Indah Ripai Dalimunthe; Jalaluddin Pane (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The scholarship selection process in universities is often still carried out manually, potentially leading to subjectivity and inaccuracy in decision-making. This study aims to develop a web-based Decision Support System to assist in determining scholarship recipients more objectively using the Simple Additive Weighting method. The SAW method was chosen because it can perform multi-criteria calculations through a simple process while maintaining accurate results. The system was developed using the CodeIgniter 4 framework and a MySQL database. Testing involved 50 prospective Bidikmisi scholarship recipients using five criteria: GPA, parental income, number of dependents, non-academic achievements, and distance from residence to campus. Results indicate that the system provides recommendations with 94 percent accuracy compared to manual decisions and reduces selection time from several days to less than one working day efficiently and consistently. Furthermore, the system enhances transparency, minimizes bias, and supports faster administrative decision making for fair scholarship distribution processes overall.